Incidencia del peso y densidad de siembra en el crecimiento y supervivencia de litopenaeus vannamei en cultivo. - Calozuma Vicente, Byron Andres; Garcia Castillo, Hans Luis (Machala : Universidad Técnica de Machala, 2024)
The research analyzed the incidence of initial weight and seeding density on the growth and survival of Litopenaeus vannamei, with the objective of optimizing production in aquaculture systems. It was carried out in the province of El Oro, Machala, in a controlled culture system. A completely randomized factorial design (2×3) was used, considering three initial weights (0.25 g, 0.5 g and 1 g) and two planting densities (10 and 20 shrimp/m²), with three replicates per treatment, for a total of 18 experimental units. Iron cages with green mesh were constructed to prevent the escape of the organisms, which were strategically located in the pond to guarantee adequate water circulation. Postlarvas from the laboratory were used and a feeding protocol based on commercial tables was applied. During the research, water quality parameters such as temperature, dissolved oxygen, pH and salinity were monitored, as well as shrimp weight and survival. Statistical analysis was performed by ANOVA using IBM SPSS software to determine significant differences between treatments. The results showed that organisms with lower initial weight (0.25 g) presented higher growth rates, especially at low densities (10 cam/m²), reaching a total weight increase of 4.58 g, 4.44 g and 4.28 g for initial weights of 0.25 g, 0.5 g and 1 g, respectively. Survival was greater than 90% in all treatments, with treatment T1 (0.25 g and 10 cam/m²) maintaining 100% survival. It is concluded that initial weight significantly influences shrimp growth, and that a lower planting density favors survival without compromising total biomass. These findings can be used to improve management strategies in cash crops, optimizing the productive yield of L. vannamei.
En la investigación se analizó la incidencia del peso inicial y la densidad de siembra en el crecimiento y supervivencia del Litopenaeus vannamei, con el objetivo de optimizar la producción en sistemas acuícolas. Se llevó a cabo en la provincia de El Oro, cantón Machala, en un sistema controlado de cultivo. Se empleó un diseño factorial completamente al azar (2×3), considerando tres pesos iniciales (0.25 g, 0.5 g y 1 g) y dos densidades de siembra (10 y 20 camarones/m²), con tres repeticiones por tratamiento, sumando un total de 18 unidades experimentales. Se construyeron jaulas de hierro con malla verde para evitar el escape de los organismos, las cuales fueron ubicadas estratégicamente en el estanque para garantizar una adecuada circulación del agua. Se utilizaron postlarvas provenientes de un laboratorio y se aplicó un protocolo de alimentación basado en tablas comerciales. Durante la investigación, se monitorearon parámetros de calidad de agua como temperatura, oxígeno disuelto, pH y salinidad, además del peso y la supervivencia de los camarones.
Keywords: LITOPENAEUS VANNAMEI; CRECIMIENTO; SUPERVIVENCIA; DENSIDAD SIEMBRA